Analisis proksimat tepung daging buah labu kuning (Cucurbita moschata) - Dokri Gumolung (Jurnal Kimia Fullerene, 2019)
The purpose of this study was to measure the levels of protein, fat, fiber, carbohydrates, water and ash, in meat flour from pumpkin fruit. Pumpkin is a nutrient-rich food needed by humans. Consumer knowledge of the nutritional content of pumpkin fruit which is still minimal makes pumpkin fruit categorized as a minor food commodity. This research was carried out using laboratory analysis methods with the following stages, determination and sampling, sample preparation, protein content analysis of the gunning method, fat content with the soxhlet method, method fiber content SNI 01-2891-1992, carbohydrate content and water content and ash by oven drying method. The results showed that pumpkin from yellow pumpkin had a protein content of 4.28%, 0.18% fat, 0.93% fiber, 83.18% carbohydrate, 6.75% water and ash 4.68%. The results of this study concluded that pumpkin fruit flour can be made as food fortification ingredients to increase the nutritional value of food ingredients.